Krüpple‐like factor 5 is essential for mammary gland development and tumorigenesis. Issue 4 (5th November 2018) - Liu, Rong; Shi, Peiguo; Zhou, Zhongmei; Zhang, Hailin; Li, Wei; Zhang, Hong; Chen, Ceshi
Abstract: Krüpple‐like factor 5 (KLF5) is required for the development of the embryo and multiple organs, such as the lung and intestine. KLF5 plays a pro‐proliferative and oncogenic role in several carcinomas, including breast cancer. However, its role in normal mammary gland development and oncogenesis has not been elucidated in vivo . In this study, we used mammary gland‐specific Klf5 conditional knockout mice derived by mating Klf5 ‐LoxP and MMTV‐ Cre mice. The genetic ablation of Klf5 suppresses mammary gland ductal elongation and lobuloalveolar formation. Klf5 deficiency inhibits mammary epithelial cell proliferation, survival, and stem cell maintenance. Klf5 promotes mammary stemness, at least partially, by directly promoting the transcription of Slug . Finally, Klf5 depletion suppressed PyMT‐induced mammary gland tumor cell stemness, tumor initiation, and growth in vivo . Slug also mediated these functions of Klf5 in vivo . Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.